Prevalence and Predictors of Climacturia and Associated Patient/Partner Bother in Patients with History of Definitive Therapy for Prostate Cancer. Issue 6 (13th March 2020) - Jimbo, Masaya; Alom, Manaf; Pfeifer, Zachary D.; Haile, Eiftu S.; Stephens, Dane A.; Gopalakrishna, Ajay; Ziegelmann, Matthew J.; Viers, Boyd R.; Trost, Landon W.; Kohler, Tobias S.
Abstract: Background: Climacturia is an under-reported complication of definitive therapy for prostate cancer (PCa) - that is, radical prostatectomy (RP) and/or radiation therapy (RT). Aim: We sought to identify the prevalence and predictors of climacturia and associated patient/partner bother in patients with and without prior PCa treatment. Methods: We analyzed a database of patients who presented to our Men's Health clinic and filled out a questionnaire related to sexual function and pertinent medical histories. The prevalence of climacturia and associated patient/partner bother in patients with/without prior RP/RT was calculated. Univariable and multivariable logistic regressions were performed to identify predictors associated with climacturia and patient/partner bother. Outcomes: The primary outcomes were the prevalence and predictors of climacturia and associated patient/partner bother in patients with/without history of definitive PCa treatment. Results: Among 1, 117 patients able to achieve orgasm, 192 patients (17%) had prior history of definitive therapy for PCa (RP alone = 139 [72%]; RT alone = 22 [11%]; RP + RT = 31 [16%]). Climacturia was reported by 39%, 14%, 52%, and 2.4% of patients with history of RP alone, RT alone, RP + RT, and neither RP nor RT, respectively ( P  < .05 between all groups). 33 to 45 percent of patients with climacturia noted significant patient/partner bother. Factors significantly associated with climacturia were prior RP, prior RT, history of other prostate surgery, and erectile dysfunction, although erectile dysfunction was not significant on multivariable analysis. Significant reduction in climacturia prevalence was noted for patients who were ≥1 year out from RP, compared with patients who were <1 year out. Among patients with prior RP/RT, stress urinary incontinence was associated with increased risk of climacturia, whereas diabetes was associated with decreased risk. No factors were associated with patient/partner bother. Among patients with prior RP, nerve-sparing technique did not predict presence of climacturia but was associated with reduced patient/partner bother. Clinical translation: Given significant prevalence of climacturia and associated patient/partner bother, patients should be counseled on the risk of climacturia before undergoing RP/RT. Strengths and limitations: Strengths include the large study population and the focus on both RP and RT. Limitations include the facts that this is a single-institution study that primarily relies on patients' subjective reporting and that the study population may not represent the general population. Conclusions: Climacturia affects a significant proportion of patients with history of RP/RT for PCa, and many patients and their partners find this bothersome.